Exogenous melatonin's effect on salivary cortisol and amylase: A randomized controlled trial - Praewpat Pachimsawat; Piyanee Ratanachamnong; Nattinee Jantaratnotai (Wiley, 2024)
Abstract This study aimed to examine the effect of acute exogenous melatonin administration on salivary cortisol and alpha‐amylase (sCort and sAA) as representatives of the HPA axis and the sympathetic nervous system, respectively. A single‐dose prolonged‐release melatonin (2 mg) or a placebo tablet was given to healthy volunteers (n = 64) at 20:00 h in a crossover design. The saliva was collected at six time points (20:00, 21:00, awakening, 30 min after awakening, 10:00, and 12:00 h) and was measured for sCort, sAA, and salivary melatonin (sMT) levels. Pulse rates and sleep parameters were also collected. Melatonin was effective in improving sleep onset latency by 7:04 min (p = .037) and increasing total sleep time by 24 min (p = .006). Participants with poor baseline sleep quality responded more strongly to melatonin than participants with normal baseline sleep quality as they reported more satisfaction in having adequate sleep (p = .017). Melatonin administration resulted in higher sCort levels at awakening time point (p = .023) and a tendency of lower sAA levels but these were not significant. Melatonin ingestion at 20:00 h resulted in a marked increase in sMT levels at 21:00 h and remained higher than baseline up to at least 10:00 h (p < .001). Melatonin increases sCort levels at certain time point with a tendency to lower sAA levels. These opposing effects of melatonin suggested a complex interplay between melatonin and these biomarkers. Also, the results confirmed the positive acute effect of a single‐dose melatonin on sleep quality.